Research progress on nursing of postoperative delirium in the elderly patients with femoral neck fracture (老年股骨颈骨折术后谵妄的护理研究进展) - LI Jiao (李姣); HU Hairong (胡海荣); LI Meilian (李美连); JIA Zongyi (贾宗祎) (Association of Integrative Nursing, 2022)
Postoperative delirium is a common complication affecting the rehabilitation of patients undergoing surgery for the femoral neck fracture, This paper introduced the relevant assessment of delirium, combed the elderly femoral neck fracture from several aspects the influence factors of postoperative delirium, and summarized the prevention and nursing measures of postoperative delirium, in order to provide the reference for the prevention of postoperative delirium and improvement of postoperative rehabilitation in the elderly patients with femoral neck fracture. (术后谵妄是影响老年股骨颈骨折患者术后康复的常见并发症。本文介绍了术后谵妄的相关评估方法, 从多个方面梳理了老年股骨颈骨折术后谵妄的影响因素, 并在此基础上对老年股骨颈骨折术后谵妄的预防及护理措施进行了总结, 旨在为预防老年股骨颈术后谵妄的发生、实施干预策略提供更多的参考依据。)